The Flexural Strength and Impact Toughness of Bamboo Reinforced Latex-Asphalt Composite - Frisko Yulian Maheswara; Akhmad Basuki Widodo; Bagiyo Suwasono (International Journal of Marine Engineering Innovation and Research, 2023)
Dependence on materials for the small ship industry can cause other problems. The development of cheap, environmentally friendly, and sustainable small ship manufacturing raw materials is a challenge that must be faced, this gave rise to the idea of developing asphalt-matrixed bamboo (Gigantochloa apus) composite materials with added latex (Hevea brasiliensis) as small ship hull skin material. The asphalt-latex composite material reinforced with apus bamboo fibers was tested using a three-point bending test and a Charpy-type impact test concerning ASTM. The test results showed that the asphalt-latex composite material reinforced with bamboo fibers had an impact toughness of 57.2 kJ/m² and a flexural strength of 6.4 MPa.